Enhancing Students’ English Speaking Skills through Toastmaster Program - Lusi Suryani (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: This study aimed to fid out if Toastmaster can enhance students’ speaking skills and its contribution to the speaking score and the siginifiant diffrence between the experimental and control group. The research involved twenty students of SMA Negeri 10 Palembang as an experimental group. The students in experimental group were given English instruction through Toastmaster. To measure the result, the researcher used a pre-test and a post-test. The result of the test showed the Toastmaster could enhance the students’ speaking skill (tcount = 4.728) and P.0.000). It means that the research hypothesis was accepted while the null hypothesis was rejected, with contribution of 19.4% to the total speaking score (based on the regession analysis). According to the result of the calculation of indepedent sample t-test (tcount = 4.755 and P.0.000), it is clear that Toastmaster gave a signifiant diffrence in enhancing students’ speaking skill.Keyword: English, speaking skill, toastmasterAbstrak: Penelitian ini bertujuan untuk mengetahui apakah Toastmaster dapat meningkatkan keterampilan berbicara Bahasa Inggris siswa dan kontribusinya terhadap skor berbicara (speaking) dan perbedaan antara kelompok eksperimen dan kelompok kontrol. Penelitian ini melibatkan dua puluh siswa SMA Negeri 10 Palembang sebagai kelompok eksperimen. Siswa pada kelompok eksperimen diberikan pengajaran Bahasa Inggris melalu Toastmaster. Untuk mengukur hasilnya, peneliti menggunakan pre-test dan post-test. Hasil test menunjukkan bahwa Toastmaster dapat meningkatkan keterampilan berbicara Bahasa Inggris siswa (tcount= 4,728) dan P,0,000). Artinya bahwa research hipothesis (HA) diterima sedangkan null hipothesis (H0) ditolak, dengan kontribusi sebesar 19,4% terhadap total skor berbicara (berdasarkan Regression Analysis). Berdasarkan hasil perhitungan Independent sample t-test (tcount= 4,755 dan P,0,000), jelas bahwa Toastmaster memberikan pengaruh signifian terhadap peningkatan keterampilan berbicara Bahasa Inggris siswa.Kata-kata kunci: Bahasa Inggris, keterampilan berbicara, toastmaster